Effects of Flight Heights and Nozzle Types on Spray Characteristics of Unmanned Aerial Vehicle (UAV) Sprayer in Common Field Crops - Saurav Ranabhat; Randy Price (AgriEngineering)
Effective spraying is an important component of precision agriculture, directly influencing the efficiency of the spray materials. Despite their potential, optimal settings for sprayer drones remain underexplored due to limited research data. This study evaluates the effects of various flight heights and nozzle types on spray characteristics in cotton, soybean, and sugarcane crops using an unmanned aerial vehicle (UAV) sprayer. Three different flight heights and two or three nozzle types were evaluated for their impacts on spray deposition, coverage percentage, and droplet size distribution at three different canopy levels of these crops. The results indicated that lower flight heights significantly increased spray deposition and coverage in the upper canopy levels of cotton and sugarcane. Centrifugal nozzles consistently produced greater coverage and spray deposition in sugarcane. Some significant interactions among these factors were also explored. The findings highlight the potential for UAV sprayers to optimize spraying in crops with various morphologies by adjusting flight height and nozzle type.